2021
DOI: 10.1523/jneurosci.2814-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Non-Linear Mixed Selectivity in Prefrontal Cortex after Training

Abstract: Neurons in the PFC are typically activated by different cognitive tasks, and also by different stimuli and abstract variables within these tasks. A single neuron's selectivity for a given stimulus dimension often changes depending on its context, a phenomenon known as nonlinear mixed selectivity (NMS). It has previously been hypothesized that NMS emerges as a result of training to perform tasks in different contexts. We tested this hypothesis directly by examining the neuronal responses of different PFC areas … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…Our results are consistent with another recent study from our laboratory which documented emergence of NMS in the PFC after training to perform working memory tasks for the first time, in a different cohort of animals ( Dang et al, 2021 ). In both of these studies, the percentage of neurons that exhibited NMS was modest, and nearly absent in some task variants ( Dang et al, 2021 ). Furthermore, lower NMS was not predictive of error trials, as would be expected by the suggested role of NMS in regulating flexible behavior ( Rigotti et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are consistent with another recent study from our laboratory which documented emergence of NMS in the PFC after training to perform working memory tasks for the first time, in a different cohort of animals ( Dang et al, 2021 ). In both of these studies, the percentage of neurons that exhibited NMS was modest, and nearly absent in some task variants ( Dang et al, 2021 ). Furthermore, lower NMS was not predictive of error trials, as would be expected by the suggested role of NMS in regulating flexible behavior ( Rigotti et al, 2013 ).…”
Section: Discussionsupporting
confidence: 93%
“…However, even prefrontal NMS was present in only a small percentage of neurons, did not result in a substantial rotation of the population responses in PCA space, and lower magnitude on a trial-to-trial basis was not predictive of errors in task execution. These findings suggest that the role of NMS is somewhat limited and that this is not the only mechanism through which complex tasks are represented in neural activity, in agreement with other recent studies ( Dang et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations